Spectrophotometric Determination of Chlorpromazine HCl by Oxidative Coupling Method in Pharmaceutical formulations - Abdul Majeed Khorsheed Ahmed; Mohsen Hamza Baker; Noor Aladdin Hussein (Tikrit Journal of Pure Science)
The research includes the development of spectrophotometric method for determination microgram amounts of CPZ via oxidative coupling with the Sodium sulphacetamide reagent in presence of oxidizing agent potassium persulphate in the acidic medium (pH=1.8) to form a violet colored-dye, which is soluble in water and showed the highest intensity of absorption at λ max 550 nm. The method has been obeyed Beer's Law in the concentration range (2 - 20) µg/ml, with molar absorptivity of 1.2791 ×104  L/ mol. Cm, Sandel Index value 0.0278 µg/cm2. The detection limit 0.1727 µg/ml, with correlation coefficient 0.9983, the relative standard deviation of the method does not exceed 0.8933%, the proposed method was applied successfully for the determination of chlorpromazine hydrochloride in pharmaceutical preparation